264 A rare cause of young stroke diagnosed by intracranial MR vessel wall imaging. Issue 12 (14th November 2019) - Aggarwal, Veena; Benjamin, Laura; Simister, Robert
Abstract : Current stroke guidelines do not facilitate the expedient diagnosis of inflammatory stroke. At UCLH, we have integrated intracranial vessel wall imaging (iVWI) into our stroke pathway to overcome this barrier. We present a case, where iVWI facilitated the diagnosis and helped us interpret a further asymptomatic stroke event. A 36-year-old man presented with left sided facial weakness. He had type 2 diabetes, hypertension, obesity, and hypercholesterolaemia. CT showed a right MCA/ACA infarct with severe bilateral ICA stenosis. MRI confirmed a borderzone infarct. The patient was treated with anti-platelets, a statin and continued ramipril and amlodipine. iVWI imaging identified an unexpected inflammatory vasculopathy. His CSF was supportive of CNS inflammation, and thus, commenced on prednisolone and empirical valaciclovir. His 3-month interval scan showed new asymptomatic borderzone infarcts that were concordant with hypoperfusion injury, and temporally linked with the initiation of indapamide by his GP, this was subsequently stopped. His vasculopathy remained static. A six-month interval scan showed no new lesion, and improvement of his inflammatory vasculopathy. Using iVWI, we were able to diagnose an inflammatory vasculopathy that could have been missed. The case also highlighted that excessive early reduction of blood pressure can contribute to hypoperfusion related stroke.